2013
DOI: 10.5535/arm.2013.37.3.336
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Abdominal Obesity in Persons With Spinal Cord Injury

Abstract: ObjectiveTo investigate the characteristics of community-dwelling spinal cord injury (SCI) persons with obesity, including diet, socioeconomic factors, weight reduction method, and frequency of body weight and abdominal circumference measurements.MethodsWe developed a questionnaire based on 'the Fourth Korea National Health and Nutrition Examination Survey, 2009'. A total of 371 community-dwelling SCI persons were enrolled in this study. Inclusion criteria were SCI persons older than 20 years with more than 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…FMP is potentially a more appropriate way of clinical diagnosis of obesity in SCI patients. Similarly, Kim et al [ 29 ] reported significantly higher number of obesity cases in complete motor paralysis than incomplete motor injury and concluded that the higher obesity rate in complete injury is the result of considerable limitation of activity in these patients.…”
Section: Discussionmentioning
confidence: 97%
“…FMP is potentially a more appropriate way of clinical diagnosis of obesity in SCI patients. Similarly, Kim et al [ 29 ] reported significantly higher number of obesity cases in complete motor paralysis than incomplete motor injury and concluded that the higher obesity rate in complete injury is the result of considerable limitation of activity in these patients.…”
Section: Discussionmentioning
confidence: 97%
“…11,44 As regards long-term outcomes, a study based on a questionnaire reported that the prevalence of obesity was not significantly different for various income groups (p = 0.39). 21 Paradoxically, one recent cohort study reported a higher mortality rate among patients in the $40,000-$60,000 income range than that among patients with less than $40,000. 7 In addition, a higher income has been associated with heavy alcohol use.…”
Section: Incomementioning
confidence: 99%
“…con IMC > 22 kg/m2. A todo ello hay que añadir las dificultades para realizar una determinación precisa de talla y peso en estos pacientes (Kim et al, 2013). Este hecho contribuye a explicar, al menos en parte, que los pacientes con LMC demuestren un escaso interés por su peso corporal de manera que solo un 48,8% de los participantes en el estudio anteriormente referido (Kim et al) reconociera haberse pesado al menos una vez en el último año.…”
Section: Discusionunclassified